Classic American crime fiction of the 1920s - Klinger, Leslie S.; Klinger, Leslie S.; Biggers, Earl Derr, 1884-1933; Van Dine, S. S.; Queen, Ellery; Hammett, Dashiell, 1894-1961; Burnett, W. R. (William Riley), 1899-1982 (Pegasus Crime, 2018)
"A riveting collection of five of the most famous crime novels of the 1920s, presenting anew some of the most admired authors of the era... Each of the five novels included is presented in its original published form, with extensive historical and cultural annotations and illustrations..." --